Effectiveness of the 'Regating' Application in Improving Knowledge and Attitudes Towards Stunting Prevention among Adolescents - Follona, Willa; Fitriana, Shentya; Irawati, Deasy (Asosiasi Pendidikan Kebidanan Indonesia (AIPKIND), 2025)
Stunting is a condition of impaired growth due to chronic malnutrition during the First 1000 Days of Life (HPK), from conception to two years of age. According to WHO data from 2020, approximately 149.2 million children under five worldwide suffer from stunting, 53% of whom are in Asia. In Indonesia, the prevalence of stunting reaches 26.9% (Riskesdas, 2018), and in DKI Jakarta, it stands at 14.8% (SSGI, 2022). Stunting significantly impacts physical growth, cognitive development, and future productivity. One factor increasing the risk of stunting is adolescents’ lack of knowledge regarding nutrition, reproductive health, and early marriage. Choosing the appropriate educational media is crucial for reaching adolescents. Web-based educational applications offer several advantages, such as broad accessibility, ease of use, and the ability to deliver engaging interactive content. This media allows adolescents to access information anytime and anywhere, making the learning process more flexible and effective. This study aims to analyze the effectiveness of stunting prevention education using the Regating application compared to the Booklet in improving adolescent knowledge and attitudes. The research design is a quasi-experiment with a control group, using pretest and posttest methods. The sample consisted of 100 female adolescents who had never received stunting education and owned a mobile phone, selected randomly. Data analysis was performed using the Paired Sample T-Test for paired groups and the Unpaired T-Test for unpaired groups. The results show a significant increase in students' knowledge and attitudes after the intervention. Knowledge scores increased by 6.876 points in the Booklet group and 9.878 points in the Regating group. Attitude scores increased by 5.98 points in the Booklet group and 16.72 points in the Regating group. The p-value of 0.000 indicates a statistically significant difference. The Regating application proved more effective than the Booklet in improving students' knowledge and attitudes toward stunting prevention. In conclusion, a web-based application can serve as an effective educational tool if implemented sustainably and supported by various stakeholders to break the intergenerational cycle of stunting. This includes integrating the application into school education programs, using it as an educational resource for health professionals, and promoting it for community and parental education.